Teacher Perception of ICT and Alpha Generation Student - Pierre Senjaya; John Tampil Purba; Rizaldi Parani; Martinus Tukiran (Universitas Cokroaminoto Palopo, 2021)
Teachers can address the global demand for technology-based teaching and learning tools and equipment to replace traditional teaching techniques by integrating Information and Communication Technology (ICT). In Indonesia, information, and communication technology (ICT) is regarded as one of the most critical components in the country's future development and success. As part of the present teaching blueprint, the Ministry of Education has embraced technology-based education and learning in its national curriculum (2013-2025). The goal of this study was to find out what teachers thought about the value of ICT integration in aiding the alpha generation's education and learning process. A survey was given to 107 Tangerang private school teachers at random. We used SPSS (version 26) to analyze the data from this quantitative study for descriptive and inference statistics. The findings of this study show that integrating ICT is beneficial to both teachers and students. According to the findings, adequate teacher preparation with ICT tools and equipment is one of the most critical elements for the efficacy of technology-based education and learning. In this study, we also discovered that teacher continuing education programs have a significant impact on increasing student learning quality. Other aspects of ICT integration need to be considered in future studies, especially from a management perspective, in terms of strategic planning and policy making for alpha generation students.